Serum Soluble B Cell-Activating Factor Is a Non-Invasive Biomarker of Antibody-Mediated Rejection in Kidney Allograft With Satisfactory Risk Stratification Performance But Negligible Diagnostic Value - Wu, Shenghui; Su, Xiaojun; Ye, Qianyu; Wei, Yongcheng; Gao, Yifang; Huang, Mingchuan; Chen, Yanxu; Wang, Jiali; Zhang, Qiang; Fu, Qian; Li, Jun; Wu, Chenglin; et al. (Frontiers in Immunology, 2022)
Objectives: B cell activating factor (BAFF), which is critical in activation and differentiation of B cell, is a candidate diagnostic and predictive biomarker for antibody-mediated rejection (ABMR). We aimed to investigate the value of serum soluble BAFF (sBAFF) for the diagnosis and risk stratification of ABMR after kidney transplantation. Methods: In the diagnostic study, sBAFF level among ABMR (n = 25), T cell-mediated rejection (TCMR) (n=14), 4 other pathological lesions (n = 21) and stable allograft function group (n = 15) were compared. In the nested case-control study, kidney allograft recipients with de novo DSA or ABMR (n = 16) vs. stable allograft function (n = 7) were enrolled and sBAFF was measured preoperatively, at D7, M1, M3, M6, M9, M12, M18 post-transplant and at allograft biopsy. Results: There was no significant difference in sBAFF level at biopsy between ABMR and non-ABMR groups. Longitudinal study showed that the sBAFF levels decreased dramatically at D7 in both groups. The sBAFF level in DSA group started to increase within M1, while in the stable group it maintained low level until M3 and M6. The sBAFF levels of DSA group were significantly higher than that of stable group at M1 (1013.23 [633.97, 1277.38] pg/ml vs. 462.69 [438.77, 586.48] pg/ml, P = 0.005), M3 (1472.07 [912.79, 1922.08] pg/ml vs. 561.63 [489.77, 630.00] pg/ml, P = 0.002) and M6 (1217.95 [965.25, 1321.43] pg/ml vs. 726.93 [604.77, 924.60] pg/ml, P = 0.027). sBAFF levels at M3 had the best predictive value for the DSA/ABMR with the AU-ROC value of 0.908. The predictive performance of the max change rate from D7 to the peak within M3 was also excellent (AU-ROC 0.949, P = 0.580). Conclusion: We clarified by a diagnostic study that sBAFF is not a diagnostic biomarker for ABMR in kidney transplantation and revealed by a nested case-control study that sBAFF values at M3 post-transplant and dynamic changes in sBAFF within M3 post-transplant have good predictive value for the DSA/ABMR. It provides a useful tool for early screening of low-risk patients with negative preoperative DSA for the risk of developing postoperative DSA in kidney allograft recipients.